Bildung, filosofie dell’Europa e destino dell’Occidente. Passaggi filosofico-politici attraverso Adorno, Gadamer e Habermas - De Simone, Antonio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
Starting from a critical examination of the relationship between the phenomenologies of the crisis, contemporary scenarios and political ontology of the conflict, this essay aims to reconstruct some of the main philosophical-political transits within the thought and work of Theodor W. Adorno, HansGeorg Gadamer and Jürgen Habermas on the specific issues of the role of Bildung, the philosophy of Europe and the destiny of the West, considering them as fundamental and inescapable points of reference for the critical understanding of the contemporary human and political condition. Bildung; Europa; Occidente; Adorno; Gadamer; Habermas.